Surface hopping dynamics with correlated single-reference methods: 9H-adenine as a case study - Plasser, Felix; Crespo-Otero, Rachel; Pederzoli, Marek; Pittner, Jiri; Lischka, Hans; Barbatti, Mario (Journal of chemical theory and computation, 2014)
Surface hopping dynamics methods using the coupled cluster to approximated second order (CC2), the algebraic diagrammatic construction scheme to second order (ADC(2)), and the time-dependent density functional theory (TDDFT) were developed and implemented into the program system Newton-X. These procedures are especially well-suited to simulate nonadiabatic processes involving various excited states of the same multiplicity and the dynamics in the first excited state toward an energetic minimum or up to the region where a crossing with the ground state is found. 9H-adenine in the gas phase was selected as the test case.